PTH-039 Longitudinal follow-up for pancreatobiliary malignancy in patients who underwent an endoscopic ultrasound. (22nd June 2015) - On, W; Lim, Y; Patani, O; Kapoor, N
Abstract : Introduction: Endoscopic ultrasound (EUS) is commonly used in the investigation of patients for pancreatobiliary disorders in the setting of a dilated common bile duct (CBD) and/or abnormal liver function tests (LFTs). There is scant literature about the natural history of such patients who undergo an EUS and their future outcomes. We aimed to perform a longitudinal follow-up of these patients with special regards to the development of pancreatobiliary malignancy. Method: 173 patients (54 males and 119 females) with a median age of 60 (IQR 46–71) who underwent an EUS at our hospital in 2010 were identified. Patients who were referred from another hospital for an EUS were excluded as they were followed up elsewhere. Details of all endoscopic procedures were obtained from our endoscopy reporting tool. Follow-up data were retrieved from our hospital's electronic records which included blood tests, radiology reports and clinic letters. Results: The initial EUS diagnoses were: Normal (n = 100, 57.8%), gallstone disease (n = 63, 36.4%), pancreatic cancer (n = 5, 2.9%), cholangiocarcinoma (n = 1, 0.6%), intraductal papillary mucinous neoplasm (n = 1, 0.6%), gall bladder cancer (n = 1, 0.6%) and chronic pancreatitis (n = 2, 1.2%). The median follow-up time was 51 months (IQR 48–54). 1 patient was diagnosed with metastatic pancreatic adenocarcinoma after presenting with worsening abdominal pain and weight loss at 10 months from initial EUS which had showed a diagnosis of gallstone disease. No other pancreatobiliary malignancies were diagnosed in any other patients during the follow-up period aside from those already diagnosed at the time of the original EUS. Conclusion: A non-malignant diagnosis at EUS does not exclude the possibility of a malignant pancreatobiliary disease in the future. A low threshold for reinvestigating is mandated especially if there are suspicious signs and symptoms. Disclosure of interest: None Declared.